2020
DOI: 10.1038/s41598-020-73577-0
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experience with 4 years of golimumab persistence in ulcerative colitis patients

Abstract: Golimumab has demonstrated its long-term efficacy and safety in ulcerative colitis in clinical trials, but no data of long-term persistence has been published from real world. To estimate long-term persistence of golimumab, as well as factors associated with longer persistence, in patients with ulcerative colitis in real life. Observational multicentre study including adult patients with ulcerative colitis treated with golimumab and with at least twelve months of follow-up. We included 190 patients, 105 (55.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 29 publications
6
25
1
Order By: Relevance
“…Looking at the other secondary points, we confirm the favorable safety profile of GOL. In fact, we recorded AEs in 7.9% of patients, lower than that reported by other longterm real-life studies [19][20][21][22][23]. However, it is hypothesized that the high rate of primary failure, with shorter follow-up, could influence these results.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Looking at the other secondary points, we confirm the favorable safety profile of GOL. In fact, we recorded AEs in 7.9% of patients, lower than that reported by other longterm real-life studies [19][20][21][22][23]. However, it is hypothesized that the high rate of primary failure, with shorter follow-up, could influence these results.…”
Section: Discussioncontrasting
confidence: 76%
“…But real-world studies showed different results. Looking at current real-life studies, focused on GOL persistence beyond 1-2 years, the remission maintenance occurred up to 27% at the 4th year of treatment [22,23]. Significantly, the unfavorable result of this study was obtained in patients naϊve to biologic therapy, while in other studies the better performances were obtained in their own patients [19,22,23].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The treatment failures were mainly reported for GOL, which consistently remained the least frequently used anti-TNFα drug in UC and was used more frequently as a second- and third-line therapy [ 44 ]. Recent studies confirm that UC patients treated with GOL after previous failure of other anti-TNFα drugs had significantly worse outcomes [ 45 , 46 ], whereas the use of the i.v. anti-TNF IFX after failure of s.c. GOL or ADA led to better results [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, being refractory to existing medicines and disease relapse have frequently been reported ( 8 , 9 ). In the case of drug- refractory disease relapse, alternative second line therapeutic strategies are currently used ( 10 , 11 ). Currently, neutralizing TNF monoclonal antibodies have been widely accepted as one of the standard strategies for the treatment of severe steroid or immunomodulator-refractory or -dependent IBD patients ( 12 ), which results in remarkably improved rates of disease remission and mucosal healing ( 12 ).…”
Section: Introductionmentioning
confidence: 99%